Reconsidering the Prudential Filter for the Cash Flow Hedge Reserve in View of the Purpose of Banking Regulation - Alois Paul Knobloch; Felix Krauß (Credit and Capital Markets – Kredit und Kapital, 2021)
Common Equity Tier~1 capital of credit institutions is adjusted by the prudential filter for the cash flow hedge reserve according to art. 33(1)(a)~CRR. Thereby, fair value changes of hedging instruments, especially of derivatives, are neutralized by imputed fair value changes of future cash flows that are part of a cash flow hedge. However, these future cash flows are (mostly) expected to occur under market conditions and, thus, imputed fair value changes are not reflected in changes of present values derived from real transactions that exist at the time of the regulatory capital calculation. As a result, positive effects on Common Equity Tier~1 capital can be viewed critically in regard to the prudence principle of banking supervision if an initial reduction in Common Equity Tier~1 capital due to losses from hedging instruments is corrected. Furthermore, the adjustment is case specific and depends on the hedge effectiveness, which is questionable because of consistency reasons. To solve these weaknesses, we suggest to eliminate the prudential filter for the cash flow hedge reserve as a whole. This would lead to a better quality of Common Equity Tier~1 capital by improving its loss absorbency and as a side effect to a reduction in complexity enhancing supervision through regulatory authorities and market discipline. Furthermore, we demonstrate the impact that the proposed abolishment of the prudential filter for the cash flow hedge reserve would have on the Common Equity Tier~1 capital ratios of the largest European banks in 2014–2019
Keywords: G21; G38; K20; M41; 330; Cash flow hedge reserve; prudential filter; regulatory capital